2013
DOI: 10.1097/id.0b013e31829e548d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Maintenance Times of Torque Application on the Removal Torque Values to Loosen the Prosthetic Abutment Screws of External Hexagon Implants

Abstract: PURPOSE: To analyze the torque application on prosthetic abutment screws using different maintenance times, to determine an influence on the removal torque values. MATERIALS AND METH-ODS: A total of 40 external hexagon implants, 40 titanium screws, and 40 customized abutments were used. In group 1, the screws received a torque of 30 N·cm by instant torque application; in groups 2, 3, and 4, torque of 30 N·cm was applied and maintained for 10, 20, and 30 seconds, respectively. Removal torque was performed 10 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…The studyindicated that 20 second maintenance time is the preferred option when considering greater detorque values compared to the instant torque application; however, de-torque value after 30 second torque maintenance time was higher than that of 20 seconds but not significantly different 13. The studyindicated that 20 second maintenance time is the preferred option when considering greater detorque values compared to the instant torque application; however, de-torque value after 30 second torque maintenance time was higher than that of 20 seconds but not significantly different 13.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The studyindicated that 20 second maintenance time is the preferred option when considering greater detorque values compared to the instant torque application; however, de-torque value after 30 second torque maintenance time was higher than that of 20 seconds but not significantly different 13. The studyindicated that 20 second maintenance time is the preferred option when considering greater detorque values compared to the instant torque application; however, de-torque value after 30 second torque maintenance time was higher than that of 20 seconds but not significantly different 13.…”
mentioning
confidence: 78%
“…12 Moreover, 20 seconds maintenance time of torque application was found to increase the removal torque value and decrease the screw loosening by reducing the settling effect between the threads of single dental implants. 12,13 However, the effect of different maintenance time of torque application and screw loosening in full-arch implant-supported prosthesis remains uninvestigated. 12,13 However, the effect of different maintenance time of torque application and screw loosening in full-arch implant-supported prosthesis remains uninvestigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the preload should not be too large and should be within the elastic limit to prevent the screw from yielding or breaking. Previous studies have demonstrated that the ideal preload is 60%–75% of the elastic limit of the material used for fabrication of the abutment screw (Kim et al., ; Saboury, Neshandar Asli & Vaziri, ; Sella et al., ). The effect of retightening after applying the initial tightening torque has been evaluated as a method to increase joint stability (Siamos, Winkler & Boberick, ).…”
Section: Introductionmentioning
confidence: 99%
“…The SIFT algorithm has a bias by which it is more likely to assign high functionality to residues within proteins that are conserved only over a short evolutionary distance, but are highly similar within this short time-frame [21]. The Polyphen algorithm has a bias by which its likelihood of assigning functionality to a mutation is higher, if the mutated allele happens to be the allele represented in the human reference genome [25]. Each of these biases may affect the results obtained by any one measure.…”
Section: Introductionmentioning
confidence: 99%